Characterization of soybean (Glycine max) varieties as per DUS guidelines - Ramteke, Rajkumar; Murlidharan, Pooja (The Indian Journal of Agricultural Sciences, 2012)
For the establishment of distinctiveness among Indian soybean [Glycine max (L.) Merrill] varieties, 20 characters were used and presented in a simple tabular form. The varieties were characterized for 20 characters, viz. flower colour, hypocotyl anthocyanin pigmentation, seed colour, absence or presence of pod pubescence, pod pubescence colour, plant growth type, pod colour, days to maturity, seed cotyledon colour, days to 50% flowering, seed size, seed shape, leaf colour, plant height (cm), seed hilum colour, seed lusture, plant growth habit, pod shattering, leaf shape and peroxidase activity. Of the 92 soybean varieties studied, 42 varieties were found to be distinctive on the basis of eleven essential characters. Remaining 50 varieties can be classified into 19 groups. However, 13 of these groups were distinct from each other on the basis of other remaining nine characters. But one group (4 varieties, viz. MAUS 1, PK 308, PUSA 20, and PUSA 37) belonging white flowered and five groups (10 varieties, viz. RKS 18 and RAUS 5, MAUS 47 and Monetta, ADT 1 and Co 1, MACS 57 and Pusa 16, Gujarat Soybean 1 and Punjab1) belonging purple flowered could not be differentiated being similar traits and therefore it is suggested to use of other biochemical markers/ DNA finger printing. This study will be useful for breeders/ researchers/ farmers to identify soybean varieties and to seek protection under Protection of Plant Varieties and Farmers Rights Act.